Student’s knowledge of the mbkm program in the culinary education study program - Ekawatiningsih, Prihastuti; Firdausa, Ambar Rizqi; Mulyatiningsih, Endang; Palupi, Sri (Jurnal Pendidikan Teknologi dan Kejuruan, 2023)
The implementation of MBKM Program at the level of Study Program is expected to provide a good atmosphere for the development of student attention and talent. Students can hone their skills in learning situations that are innovative, flexible, based on student curiosity and interest. This study aims to see the student’s knowledge or understanding of the MBKM Program in the Culinary Education Study Program. The research was conducted using an online survey method. The subject of this research is the MBKM Program which includes: (1) MBKM Program, (2) Student Exchange activities, (3) Teaching Assistance activities, (4) Internship activities, and (5) Entrepreneurship Practice activities. This study involved 131 student respondents in the Culinary Education Study Program. Data was collected online with an answer scale of 1-5 to describe the level of student knowledge ranging from poor to very good. The survey results show that (1) the level of understanding of students in the MBKM program in general is in the good category, (2) the level of knowledge of Student Exchange activities and Teaching Assistance activities in the sufficient category, (3) the level of understanding of Internship activities and Entrepreneurship Practices in the good category, however, students experience misconceptions of understanding with similar regular activities that have been organized by the study program on a regular basis.